First post-IR IRSL dating results of Quaternary deposits from Bilogora (NE Croatia): Implications for the Pleistocene relative uplift and incision rates in the area. (20th November 2018) - Wacha, Lara; Matoš, Bojan; Kunz, Alexander; Lužar-Oberiter, Borna; Tomljenović, Bruno; Banak, Adriano
Abstract: Bilogora is a hilly terrain in the SW Pannonian Basin, along the SW margin of the Drava Depression in Croatia. It is genetically linked to the tectonic evolution of the Drava Depression during the Neogene and Quaternary and the associated palaeo-Drava River System. The Quaternary sedimentary succession is represented by four aggradational Drava River terraces composed of thick series of gravel intercalated by sand, silt and clays. Stratigraphically, the oldest terraces exposed in the investigated area are unconformably overlain by Pleistocene loess and loess-like deposits. In order to establish a chronological framework of the Quaternary deposits, luminescence dating was applied on loess and loess-like sediments as well as sand intercalated within the terrace gravel deposits. The dating was performed on feldspar coarse-grains from the sand and on the polymineral fine-grained material from loess, using the pIRIR290 protocol. The luminescence signals of the sand are in saturation and therefore very likely point to a Middle Pleistocene age of the river terrace, whereas the covering loess can be correlated to the Last Glacial. The obtained pIRIR290 dating results indicate the timing of the abandonment of the investigated river terrace, whereas the relation of the relative displacement values of the investigated river terrace to the obtained age could imply the relative uplift rates of the area. According to the relative displacement values, sampling heights above the present Drava River level and the obtained pIRIR290 ages of >359 ka and >450 ka, the calculated relative uplift rates were 0.56 mm/a for Mučna Reka and 0.43 mm/a for Cabuna. For the same sampling locations, the calculated relative incision rates of the Drava River were of 0.09 and 0.22 mm/a. The results of relative uplift rates show a higher value concentrated in the NW part of Bilogora, being associated with multiple mapped neotectonic active faults in the Drava Depression Boundary fault zone and Kalnik Mt. Fault Zone. On the other hand, the low incision rates that probably accommodate a portion of the tectonic uplift of Bilogora, point to lower erosion of the paleo-Drava River. Moreover, the Drava River is dominated by the aggradation of alluvial deposits during the Quaternary. We believe that the computed incision rates represent only one relative portion of the Drava process, whereas the tectonics, sediment transportation and accumulation were dominant processes in the study area and can be correlated with the climate oscillations during the Pleistocene and Holocene.